Using Touchscreen Tablets to Help Young Children Learn to Tell Time - Wang, Fuxing; Xie, Heping; Wang, Yuxin; Hao, Yanbin; An, Jing (Frontiers in Psychology, 2016)
Young children are devoting more and more time to playing on handheld touchscreen devices (e.g., iPads). Though thousands of touchscreen apps are claimed to be “educational,” there is a lack of sufficient evidence examining the impact of touchscreens on children’s learning outcomes. In the present study, the two questions we focused on were (a) whether using a touchscreen was helpful in teaching children to tell time, and (b) to what extent young children could transfer what they had learned on the touchscreen to other media. A pre- and post-test design was adopted. After 10 min of exposure to an iPad touchscreen app designed to teach time, three groups of 5- to 6-year-old children (N = 65) were, respectively, tested with an iPad touchscreen, a toy clock or a drawing of a clock on paper. The results revealed that post-test scores in the iPad touchscreen test group were significantly higher than those at pre-test, indicating that the touchscreen itself could provide support for young children’s learning. Similarly, regardless of being tested with a toy clock or paper drawing, children’s post-test performance was also better than pre-test, suggesting that children could transfer what they had learned on an iPad touchscreen to other media. However, comparison among groups showed that children tested with the paper drawing underperformed those tested with the other two media. The theoretical and practical implications of the results, as well as limitations of the present study, are discussed.